Dose-Dependent Variation of Synchronous Metabolites and Modules in a Yin/Yang Transformation Model of Appointed Ischemia Metabolic Networks - Qi, Yifei; Zhou, Niwen; Jiang, Qing; Wang, Zhi; Zhang, Yingying; Li, Bing; Xu, Wenjuan; Liu, Jun; Wang, Zhong; Zhu, Lixing (Frontiers in Neuroscience, 2021)
Aim: Chinese medicine Danhong injection (DHI) is an effective pharmaceutical preparation for treating cerebral infarction. Our previous study shows that DHI can remarkably reduce the ischemic stroke-induced infarct volume in a dose-dependent manner, but the pharmacological mechanism of the DHI dose-dependent relationship is not clear. Therefore, the dose-dependent efficacy of DHI on cerebral ischemia and the underlying mechanisms were further investigated in this study. Methods: A middle cerebral artery occlusion (MCAO) model was established and the rats randomly divided into 6 groups as follows: sham, vehicle, DHI dose-1, DHI dose-2, DHI dose-3 and DHI dose-4. 41 metabolites in serum were selected as candidate biomarkers of efficacy phenotypes by Agilent 1290 rapid-resolution liquid chromatography system coupled with Agilent 6550 Q-TOF MS system. Then the metabolic networks in each group were constructed using the Weighted Correlation Network analysis (WGCNA). Moreover, Yang and Yin transformation of six patterns (which defined by up- and downregulation of metabolite) and synchronous modules divided from synchronous network were used to dynamics analyze the mechanism of the drug effectiveness. Results: The neuroprotective effect of DHI is dose-effect relationship, and the high doses groups (DH3 DH4) effect is better. The entropy of metabolic network and Yin/Yang index both showed a consistent dose-response relationship. Seven dose-sensitive metabolites maintained constant inverse upregulation or downregulation in the four dose groups. Three synchronous modules for the DH1-DH4 full-course network were identified. Glycine, N-Acetyl-L-glutamate and Tetrahydrofolate as a new emerging module were appeared in the DH2/DH3 and enriched in glutamine and glutamate metabolism-related pathways. Conclusion: This study takes the DHI metabolic network as an example to provide a new method for discovery multiple targets related to pharmacological effects. Our results show that the three conservative allosteric module nodes: Taurine, L-Tyrosine and L-Leucine may be one of the basic mechanisms of DHI in treatment of cerebral infarction, and the other three new emerging module nodes: Glyoxylate, L-Glutamate and L-Valine may participate in the Glutamine and glutamate metabolism pathway to improve the efficacy of DHI.